2017
DOI: 10.21161/mjm.90916
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effects of Quercus infectoria gall extract on the cell morphology of Streptococcus agalactiae, Proteus vulgaris and Candida albicans

Abstract: Aims: Quercus infectoria (QI) gall extract is known to have broad spectrum anti-microbial activity in vitro. However, its mechanism of microbial growth inhibition is not well understood. The objectives of this study were to determine the antimicrobial effect of methanolic QI gall extract on bacteria and yeast and changes to their cell morphology. Methodology and results: The minimum inhibitory concentrations (MICs) of methanolic QI gall extract against Streptococcus agalactiae (ATCC 13813), Proteus vulgaris (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(30 reference statements)
0
1
0
Order By: Relevance
“… 24 , 26 - 28 , 41 As several studies have shown, the absolute content of tannins in any form of Qi galls extract is high. 24 , 27 - 30 , 34 , 35 , 41 Therefore, this chemical compound is believed to be the main active element responsible for its antimicrobial activity. 25 , 26 , 32 Tannin is a phenolic compound soluble in water and acetone and is precipitated by proteins.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 26 - 28 , 41 As several studies have shown, the absolute content of tannins in any form of Qi galls extract is high. 24 , 27 - 30 , 34 , 35 , 41 Therefore, this chemical compound is believed to be the main active element responsible for its antimicrobial activity. 25 , 26 , 32 Tannin is a phenolic compound soluble in water and acetone and is precipitated by proteins.…”
Section: Discussionmentioning
confidence: 99%